Memahami Sufisme: Suatu Tanggapan terhadap Beberapa Tuduhan - Kautsar Azhari Noer (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2000)
This paper seeks to dispel misunderstandings about Sufism by refuting such accusations. It will not, as scholars often do, present all aspects of Sufism, including its definition, origins, development, teachings, doctrines, practices, and other aspects. Instead, it will focus on responding to these accusations. Through this approach, the paper aims to provide a correct understanding of Sufism.